1977
DOI: 10.1093/nar/4.4.899
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mRNA-protein complexes from mammalian cells

Abstract: In a previous report we described the use of oligo(dT)-cellulose for the isolation of mRNA-protein complexes from EDTA-dissociated polysomes extracted from normally growing or adenovirus infected KB-cells (I). Experiments presented here provide evidence that proteins involved in these complexes bind specifically to mRNA since: a) the proteins and mRNA cosediment through sucrose gradients, b) they adsorb and elute from oligo(dT)-cellulose together, and c) analysis of the products from ribonuclease digestion exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
5
15
1
Order By: Relevance
“…Two identifiable regions of mRNA molecules have been proposed as putative binding sites for proteins: the 5'-terminal cap structure (30) and the 3'-OH poly(A)-stretch of the mRNA (3)(4)(5)(6)(7). We believe that other binding sites must exist since electron microscope visualization of 15 S mRNP particles showed that proteins are located at several different points along the messenger molecule (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two identifiable regions of mRNA molecules have been proposed as putative binding sites for proteins: the 5'-terminal cap structure (30) and the 3'-OH poly(A)-stretch of the mRNA (3)(4)(5)(6)(7). We believe that other binding sites must exist since electron microscope visualization of 15 S mRNP particles showed that proteins are located at several different points along the messenger molecule (8).…”
Section: Discussionmentioning
confidence: 99%
“…The 15 S globin mRNP released from polyribosomes by EDTA has a characteristic protein composition (2) which includes a major 73,000 MW polypeptide bound to the 3' terminal poly(A) segment (3), similar to that found for a variety of other messenger molecules (4)(5)(6)(7). Electron microscopy data obtained by dark-field visualization of duck globin 15 S mRNP particles has shown that proteins are distributed al ong all of the messenger molecule although not uniformly (8).…”
Section: Introductionmentioning
confidence: 97%
“…UV cross-linking of proteins to RNA in intact cells overcomes these difficulties and allows the identification of proteins which bind heterogeneous nuclear RNA and mRNA in vivo (11,16,51,54). To learn more about these proteins and about the RNP complexes, we have immunized mice with purified UV-crosslinked RNP complexes and have produced antibodies to several of the major RNP proteins in vertebrate cells (1,12,13).Much of the knowledge of RNP proteins has come from work with higher eucaryotes (12,24,48 (7) and is one of the most conserved and extensively investigated eucaryotic RNP proteins. Although many important functions in mRNA metabolism have been attributed to this protein, little is known about its function, amino acid sequence, and metabolism.…”
mentioning
confidence: 99%
“…Much of the knowledge of RNP proteins has come from work with higher eucaryotes (12,24,48 (7) and is one of the most conserved and extensively investigated eucaryotic RNP proteins. Although many important functions in mRNA metabolism have been attributed to this protein, little is known about its function, amino acid sequence, and metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation